2010
DOI: 10.1111/j.1745-6592.2010.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Chemical Oxidation of RDX‐Contaminated Groundwater with Permanganate at the Nebraska Ordnance Plant

Abstract: To evaluate the efficacy of permanganate to remove RDX under field conditions, a pilot-scale demonstration was performed in a 9 m by 15 m well field.Groundwater was extracted from a center extraction well, spiked with permanganate and bromide, and fed into two injection wells. Groundwater was then sampled biweekly for 8 weeks in monitoring wells down gradient of the injection zone. Results showed that RDX concentrations decreased 73 to 80% following injection. Despite problems encountered in getting the perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…S6B). Although the magnitude of 373 NO 3 -generated was similar to what we observed when MnCO 3 was used as a 374 quenching agent (Fig. S6A, S6B (Fig.…”
Section: Si-3 Experimental Controls 228supporting
confidence: 75%
See 1 more Smart Citation
“…S6B). Although the magnitude of 373 NO 3 -generated was similar to what we observed when MnCO 3 was used as a 374 quenching agent (Fig. S6A, S6B (Fig.…”
Section: Si-3 Experimental Controls 228supporting
confidence: 75%
“…To accurately quantify RDX and degradation product concentrations during oxidation by MnO 4 − , samples were quenched to prevent further RDX transformation. To avoid interferences during RDX and degradate analyses, three different quenching agents were tested (MnSO 4 , MnCO 3 , and H 2 O 2 ). The choice of quenching agent was found to influence pH and product distribution (see Supporting Information, SI-4).…”
Section: Methodsmentioning
confidence: 99%
“…Electrical resistivity imaging (ERI) was used to identify the location of the permanganate after injection. Despite problems in getting the permanganate evenly distributed throughout the well screen, pilotscale results showed that RDX concentrations decreased in wells closest to the injection wells by 70-80 % [405].…”
Section: Permanganatementioning
confidence: 99%
“…Regardless of the pathway, it is clear that permanganate is capable of transforming and mineralizing RDX [382,404]. To scale up these observations, Albano [405] recently conducted a pilotscale test using permanganate on a test section of RDX-contaminated groundwater at the Nebraska Ordnance Plant. The pilot-scale ISCO was performed by using an extraction/injection well configuration to create a curtain of permanganate between two injection wells.…”
Section: Permanganatementioning
confidence: 99%
“…Past work by Adam et al (2004) showed that permanganate could effectively mineralize RDX in the presence of aquifer solids. Using sediments and groundwater from the NOP, Albano (2009) performed treatability experiments and confirmed that site conditions at NOP were conducive to using permanganate as an ISCO treatment. The first objective of this study was to determine the efficacy of permanganate to transform RDX at the field scale by performing a pilot‐scale in situ chemical oxidation (ISCO) demonstration (Albano et al 2010).…”
Section: Introductionmentioning
confidence: 85%